The changing face of malnutrition and regulatory and fiscal efforts to address the rapid food system changes and growth in obesity while also improving overall diet quality - Popkin, Barry M. (2018)
Barry M. Popkin SPECIAL EVENT 28th Annual Martin J. Forman Memorial Lecture Confronting the New Face of Malnutrition: Regulatory and Fiscal Approaches to Improving Diets OCT 29, 2018 - 12:15 PM TO 01:45 PM EDT